Entamoeba gingivalis is associated with periodontal conditions in Chinese young patients: A cross-sectional study - Jiao, Junwei; Bie, Mengyao; Xu, Xin; Duan, Dingyu; Li, Yan; Wu, Yafei; Zhao, Lei (Frontiers in Cellular and Infection Microbiology, 2022)
Background: This study investigated the prevalence and relative abundance of Entamoeba gingivalis (E. gingivalis) in Chinese young patients with different periodontal conditions, and its association with subgingival microbial composition, periodontal parameters, and cytokines in gingival crevicular fluid. Methods: Participants (age: 18–45 years) diagnosed with stage II–IV periodontitis, gingivitis, or periodontal health underwent periodontal examination and sampling. Subgingival plaque was analyzed by 16S+18S sequencing for E. gingivalis detection and microbial analysis. The distribution of E. gingivalis in subgingival plaque was illustrated by fluorescence in situ hybridization. Interleukin-1β, interleukin-8, and tumor necrosis factor-α in gingival crevicular fluid were measured by multiplexed flow cytometric assay. Results: This cross-sectional study included 120 sites from 60 participants. The prevalence and relative abundance of E. gingivalis were significantly increased in periodontitis (p<0.05). The sites were classified into three subgroups according to the relative abundance of E. gingivalis: negative group (Eg0, n=56); low-abundance group (Eg1, n=32); and high-abundance group (Eg2, n=32). The subgingival microflora in the subgroups showed stepwise changes at both the phylum and genus levels. The microflora compositions were significantly altered from Eg0 to Eg2 (p<0.001). Co-occurrence network analysis showed that Porphyromonas, Treponema, Tannerella, Filifactor, TG5, and Desulfobulbus were highly correlated with E. gingivalis (r>0.6, p<0.001). Correlation analysis showed that E. gingivalis was closely associated with important periodontal parameters and cytokines (p<0.01). Conclusion: E. gingivalis was enriched in periodontitis and closely associated with subgingival microbial dysbiosis, periodontal parameters and cytokines in gingival crevicular fluid. Thus, it may be an important pathogen in periodontal disease.